Immediate direct-to-implant breast reconstruction: A single center comparison between different procedures - Klinger, Francesco; Lisa, Andrea; Testori, Alberto; Vaccari, Stefano; Bandi, Valeria; Lorenzano, Valerio; Klinger, Marco; Tinterri, Corrado; Vinci, Valeriano (Frontiers in Surgery, 2022)
Background: the increased incidence of conservative mastectomy operations (nipple- and skin- sparing) has increased the frequency of immediate breast reconstructions (IBR). In order to guarantee patients the best possible aesthetic outcome, the least chance of complications and postoperative pain, the technique with prepectoral prosthetic pocket was recently reconsidered with the use of ADM. This is the first study using Fortiva® in prepectoral breast reconstruction, and it compares the outcomes of three different patient populations (undergoing retromuscular, prepectoral and prepectoral reconstruction with ADM). The authors suggest that prepectoral breast reconstruction with ADM may bring benefits compared to the current standard technique (retromuscular) as well as compared to the prepectoral reconstruction without ADM. Methods: Retrospective data analysis of patients who underwent mastectomy followed by immediate breast reconstruction with implants (DTI), performed by a team of breast surgeons and plastic surgeons. Logistic factor regressions were performed in order to investigate the effects of the three different intervention techniques on the incidence of complications. Fisher's exact test was used to analyze the differences in the occurrence of each complication. Mann Whitney test was used to compare the averages of referred pain. A p value <0.05 was considered significant. Results: a total of 67 patients underwent DTI reconstruction, of which 43 with retromuscular prosthesis, 13 prepectoral and 11 prepectoral with ADM. We found a significantly lower incidence of surgical complications with ADM, exclusively in comparison with retromuscular reconstruction (p = 0.028). It emerges prepectoral reconstruction with ADM involves significantly less visibility of the implant than both the prepectoral surgery without ADM (p = 0.013) and the retromuscular technique (p = 0.029). Finally, postoperative pain referred at twelfth month is significantly less relevant in the group with prepectoral prosthesis and ADM. Conclusions: this study demonstrates that immediate prepectoral breast reconstruction with ADM is a safe and reliable technique, able to exceed some type of limits imposed by prepectoral reconstruction. Moreover, it provides benefits if compared to the current standard technique. In the future, this technique could also be added to it, after a proper selection of patients in pre- and intraoperative time.